2018
DOI: 10.2147/ppa.s169072
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study to evaluate infection prevention protocol in pediatric trauma patients with blunt splenic injury in a Dutch level 1 trauma center

Abstract: PurposeAsplenic patients are at increased risk for the development of overwhelming postsplenectomy infection (OPSI) syndrome. It is believed that adequate immunization, antimicrobial prophylaxis, as well as appropriate education concerning risks on severe infection lead to the decreased incidence of OPSI. The aim of this study was to analyze the methods used to prevent OPSI in trauma patients splenectomized before the age of 18.Patients and methodsA retrospective, single-center study of all pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…As pediatric splenic injury grading has low inter-radiologist variability, grading is believed to be very reliable [37]. to detect a contrast blush, indication for angio-embolization in the setting of delayed hemodynamic instability.to help guide follow-up imaging, make vaccination recommendations and help estimate discharge management [38]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pediatric splenic injury grading has low inter-radiologist variability, grading is believed to be very reliable [37]. to detect a contrast blush, indication for angio-embolization in the setting of delayed hemodynamic instability.to help guide follow-up imaging, make vaccination recommendations and help estimate discharge management [38]. …”
Section: Discussionmentioning
confidence: 99%
“…to help guide follow-up imaging, make vaccination recommendations and help estimate discharge management [38].…”
Section: Discussionmentioning
confidence: 99%
“…The study group consisted of 83 (68%) males and 38 (31%) females, with a median age of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16) and a median ISS of 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). On admission, the study group had a median SBR of 120 (108-130), a PR of 92 (80-110), and a GCS of 15 (14)(15). A total of 47 (39%) patients were transferred from a different hospital to the UMC Utrecht.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, almost all studies that performed splenic function tests showed a preserved splenic function after AE. In case of an inadequate splenic function, the infection prevention protocol should be applied [14]. However, there is still no single parameter or test available, which can demonstrate a preserved splenic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation